Two new species of the genus Xizicus Gorochov, 1993 (Tettigoniidae: Meconematinae: Meconematini) from Gaoligongshan, Yunnan, China - Cui, Peng; Liu, Qing; Shi, Fuming (Zootaxa, 2020)
The paper reports 2 new species of the genus Xizicus Gorochov, 1993 from Gaoligongshan, Yunnan, China, i.e. Xizicus (Axizicus) furcus Cui, Liu & Shi sp. nov. and Xizicus (Eoxizicus) gaoligongshanensis Cui, Liu & Shi sp. nov., and supplies characteristic photographs of external morphology. Besides, morphological illustrations of Xizicus (Eoxizicus) kulingensis (Tinkham, 1943) are provided. The type specimens are deposited in the Museum of Hebei University, Baoding, P. R. China.